Effects of Virtual Reality Based Therapeutic Exercise on the Upper Extremity Function and Activities of Daily Living in Patients with Acute Stroke: A Pilot Randomized Controlled Trial (Medico Legal Update, 2021)
Background: Virtual reality-based therapeutic exercise (VRTE) has been considered as a rehabilitativeintervention for neurological deficits. The aim of this study was to compare the effects of VRTE andoccupational therapy (OT) on the upper extremity function and activities of daily living in patients withacute stroke.Method: Twenty-four patients who had suffered a stroke within the last 30 days before enrollmentparticipated in this study. They were randomly assigned to either the VRTE group (n = 12) or the OT group(n = 12). Twenty sessions were conducted in all. To quantify the upper extremity function, the Jebsen-Taylorhand function test (JT) and Fugl-Meyer Assessment (FMA) of the upper limb were used, and the gripstrength (GS) was assessed. To assess activities of daily living, the modified Barthel index (MBI) was used.Results: In the VRTE group, JT (p = 0.002), FMA (p = 0.002), GS (p = 0.002), and MBI (p = 0.002) showeda significant improvement after the intervention. In the OT group, JT (p = 0.002), FMA (p = 0.001), GS (p= 0.002), and MBI (p = 0.001) significantly improved after the intervention. However, compared with OT,VRTE did not show significant improvements in upper extremity function and activities of daily living.Conclusions: This study suggests that the early approach of VRTE is not superior to OT for the improvementof upper limb function and activities of daily living in patients of stroke